Influence of Microphallus szidati Martorelli, 1986 (Trematoda) on the fecundity of the second intermediate host, Palaemonetes argentinus Nobili, 1901 (Decapoda: Natantia) - Merlo, Matias Javier (2016)
Parasites usually have strong negative effects on the fitness of their hosts, as in the reduction of host fecundity. We evaluated the female fecundity of Palaemonetes argentinus Nobili, 1901 from two populations with contrasting levels of parasitism: the population from Nahuel Rucá (NR), Argentina that was fully parasitized by a larval digenean (Microphallus szidati Martorelli, 1986) and the population from El Burro (EB) that was completely free of parasites. Realized and actual fecundity (i.e., number of newly spawned embryos and number of embryos ready to hatch, respectively) were higher in the parasitized females from NR. Moreover, infected females from NR produced heavier eggs than uninfected ones from EB. Egg loss (estimated as difference between realized and actual fecundity), however, was higher in the parasitized population (18.6 versus 10%). Higher egg loss is likely a negative effect of parasitism; however, the differences in fecundity between the two P. argentinus populations may be explained by differences in local ecological conditions. Future studies under controlled experimental conditions should compare realized and actual fecundity between parasitized and non-parasitized P. argentinus from a same population. Our results highlight the importance of parasitism as a biotic factor to be considered in analyzing life history traits in shrimp populations.